Keterampilan Siswa Memecahkan Masalah Olimpiade Matematika Ditinjau dari Kepribadian Tipe Senising dan Intuiting - Rohim, Mohammad Fatkur; Sari, Anisa Fatwa (Jurnal Elemen, 2019)
This study aims to determine the problem-solving skills of olympiad mathematics based on sensing and intuitive personality types. The study was conducted at a private junior high school in the city of Surabaya. The subjects of this study were 2 students with sensing intuitive personality taken from students who were given the Mathematics Olympiad training, namely 1 student with sensing personality and 1 student with intuitive personality. Olympiad questions are given to explore the skills of both subjects in solving problems. The results of research students who have sensing personality (S1) are less able to define a particular topic on the question, S1 is able to work with a structure based on what is recognized, S1 has difficulty with the related topics that are being solved with other topics. S1 has difficulty in determining other solutions related to the problem being solved. Students who have the intuitive personality (S2) are able to define the meaning of a particular topic on the problem, S2 is able to link the topic to the problem with other topics, S2 is able to explain other solutions to the problems solved, S2 is able to present a more structured solution.